2008
DOI: 10.1016/j.virusres.2008.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of virus factories purified from Rabbit vesivirus-infected Vero cells

Abstract: a b s t r a c tRabbit vesivirus infection induces membrane modifications and accumulation of vesicular structures in the cytoplasm of infected Vero cells. Crude RaV replication complexes (RCs) have been purified and their structural and functional properties have been characterized. We show that calnexin, an ER-resident protein, RaV non-structural proteins 2AB-, 2C-, 3A-, 3B-and 3CD-like as well as viral RNAs co-localize within membranous structures which are able to replicate the endogenous RNA templates. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
(54 reference statements)
0
8
0
Order By: Relevance
“…Varicella zoster virus infection provides an excellent example of autophagy in humans, because abundant autophagosomes are easily detected in the skin vesicles of both varicella and zoster . Autophagy is also found during viral replication of HCV , rabbit calicivirus and poliovirus . Given that melatonin modulates autophagy through redox‐sensitive transcription factors , the role of melatonin in such viral infections involving autophagy should be examined.…”
Section: Melatonin As a Regulator Of Programmed Cell Death In Viral Imentioning
confidence: 99%
“…Varicella zoster virus infection provides an excellent example of autophagy in humans, because abundant autophagosomes are easily detected in the skin vesicles of both varicella and zoster . Autophagy is also found during viral replication of HCV , rabbit calicivirus and poliovirus . Given that melatonin modulates autophagy through redox‐sensitive transcription factors , the role of melatonin in such viral infections involving autophagy should be examined.…”
Section: Melatonin As a Regulator Of Programmed Cell Death In Viral Imentioning
confidence: 99%
“…NS7 is an RNA-dependent RNA polymerase (RdRp), also known as a viral replicase (reviewed in [25]). NS1/2 and NS4 have not been fully characterized but it has been hypothesized that, as they contain membrane-spanning hydrophobic domains, they might be involved in the rearrangement of cell organelle membranes during the assembly of membrane-associated virus replication factories [44]. It has also been suggested that they act as virulence factors (e.g., viroporins and antiviral immune response suppressors), thus playing roles in viral pathogenicity and epidemiological fitness (for a comprehensive review of calicivirus non-structural proteins and their analogs in picornaviruses, refer to Smertina et al [45]).…”
Section: The Caliciviridae: Genome Organization Gene Expression and R...mentioning
confidence: 99%
“…Lagoviruses, such as rabbit hemorrhagic disease virus (RHDV) and rabbit vesivirus (RaV), induce autophagosome and autophagolysosome formation . During RHDV‐induced autophagy, increased expression of Beclin1, LC3‐II/LC‐I ratio and Atg5‐Atg12‐Atg16L1, as well as colocalization of LC3 and LAMP‐1, were reported.…”
Section: Virus Infectionmentioning
confidence: 99%